An Unusual Presentation of Adult Tethered Cord Syndrome Associated with Severe Chest and Upper Back Pain. (9th September 2015) - Kanda, Shotaro; Akiyama, Toru; Chikuda, Hirotaka; Yamaguchi, Takehiko; Saita, Kazuo
Abstract : Adult tethered cord syndrome (ATCS) is a rare entity that usually presents with multiple neurological symptoms, including lower extremity pain, backache, lower extremity muscle weakness, and bowel/bladder disturbances. Prompt surgical treatment is often necessary to avoid permanent sequelae. We report a 63-year-old man with sudden-onset severe right chest and upper back pain, followed by urinary retention. His initial workup included computed tomography of the abdomen and pelvis, which showed a presacral mass. His symptom-driven neurological workup focused on the cervical and thoracic spine, the results of which were normal. Pelvic radiographs and magnetic resonance imaging of the lumbosacral spine showed spina bifida occulta, meningocele, and presacral masses consistent with a teratomatous tumor. His symptoms, except for urinary retention, improved dramatically with surgical treatment. The excised specimen contained a teratomatous lesion plus an organized hematoma. Hematoma formation was suspected as the trigger of his sudden-onset right chest and upper back pain.